2009
DOI: 10.1519/jsc.0b013e3181a2b8a2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a 7-Week Heavy Elastic Band and Weight Chain Program on Upper-Body Strength and Upper-Body Power in a Sample of Division 1-AA Football Players

Abstract: The purpose of this study was to explore the effects of a 7-week heavy elastic band and weighted-chain program on maximum muscular strength and maximum power in the bench press exercise. Thirty-six (n = 36) healthy men aged 18-30 years old, from the Robert Morris University football team, volunteered to participate in this study. During the first week, predicted 1 repetition maximum (1RM) bench press and a 5RM speed bench press tests were conducted. Subjects were randomly divided into 3 groups (n = 12): elasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 11 publications
3
88
0
Order By: Relevance
“…The authors reported that all three groups significantly improved their 1RM strength with no significant differences established between groups. Ghigiarelli et al, (19) also reported greater non-significant improvements in peak power for the variable resistance groups. Combining the results obtained by McCurdy et al, (27) and Ghigiarelli et al,(19) it is evident that chains can be combined with free-weight resistance to improve strength.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The authors reported that all three groups significantly improved their 1RM strength with no significant differences established between groups. Ghigiarelli et al, (19) also reported greater non-significant improvements in peak power for the variable resistance groups. Combining the results obtained by McCurdy et al, (27) and Ghigiarelli et al,(19) it is evident that chains can be combined with free-weight resistance to improve strength.…”
Section: Discussionmentioning
confidence: 91%
“…Ghigiarelli et al, (19) also reported greater non-significant improvements in peak power for the variable resistance groups. Combining the results obtained by McCurdy et al, (27) and Ghigiarelli et al,(19) it is evident that chains can be combined with free-weight resistance to improve strength. In addition, it appears that the inclusion of chains may provide additional advantages over a constant barbell resistance for certain biomechanical and physiological variables.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The increase in popularity of intra-repetition (Soria-Gila, Chirosa, Bautista, Chirosa, & Salvador, 2015) variable resistance exercise applied via chains and rubber, elastic bands (Baker & Newton, 2005;Heinecke, Jovick, Cooper, & Wiechert, 2004;Simmons, 1996Simmons, , 1999Swinton, Lloyd, Agouris, & Stewart, 2009;Warpeha, 2002) coupled with the varied, inconsistent adaptations reported with these loading methodologies (Anderson, Sforzo, & Sigg, 2005;Ghigiarelli, et al, 2009;McCurdy, Langford, Ernest, Jenkerson, & Doscher, 2009;Rhea, Kenn, & Dermody, 2009;Shoepe, Ramirez, Rovetti, Kohler, & Almstedt, 2011) mandates a more valid and careful examination of training volume during variable resistance applications. This is due to traditional free-weight exercises producing linear loading patterns, whereas variable resistance, as incurred by rubber-bands, exhibit nonlinear loading patterns (McMaster, Cronin, & McGuigan, 2009;Mcmaster, Cronin, & McGuigan, 2010;Shoepe, Ramirez, & Almstedt, 2010;Thomas, Mueller, & Busse, 2005).…”
Section: Introductionmentioning
confidence: 99%